Restorative practices in reducing school violence: a systematic review of positive impacts on emotional wellbeing - Alonso-Rodríguez, Isabel; Pérez-Jorge, David; Pérez-Pérez, Itahisa; Olmos-Raya, Elena (Frontiers in Education, 2025)
IntroductionRestorative practices (RP) have been implemented in educational settings to reduce school violence and improve emotional wellbeing and group cohesion. This systematic review examines their effectiveness in the school context.MethodWe searched Scopus and Web of Science, selecting 13 studies that met specific inclusion criteria. The studies analyzed included diverse methodologies and populations, mainly from the United States and the United Kingdom.ResultsFindings indicate that RP reduces violence, improves emotional wellbeing, and promotes socio-emotional skills. However, the predominance of quantitative approaches and the need for longitudinal studies limit the in-depth understanding of their sustained effects.ConclusionRP positively impacts school climate, although further research in varied contexts and with mixed methodologies is recommended to assess its long-term sustainability. Schools should implement RP gradually, integrating students, teachers, and families. The implication of this study focuses on making visible alternative disciplinary approaches that not only regulate behavior appropriately but also foster a culture based on peace, inclusion and respect in the educational environment. The information obtained will help educational institutions to create informed policies and programs that promote a safe and inclusive environment, fostering the holistic development of students and supporting the creation of a culture of peace in schools.